2020
DOI: 10.1186/s12955-020-01340-0
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and its association with current substance use, medication non-adherence and clinical factors of people with schizophrenia in Southwest Ethiopia: a hospital-based cross-sectional study

Abstract: Background: Schizophrenia was ranked as one of the top ten illnesses contributing to the global burden of disease. But little is known about the quality of life among people with schizophrenia, in particular in low-income countries. This study was aimed to examine the association of quality of life with current substance use, medication non-adherence and clinical factors of people with schizophrenia at Jimma University Medical Center, psychiatry clinic, Southwest Ethiopia. Methods: Institution based cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 28 publications
(37 reference statements)
7
10
0
Order By: Relevance
“…When we examined the independent association of each physical health condition and disability within groups, our results suggested that sociodemographic factors could have a greater impact in these associations in individuals with SSD. Although our results are not directly comparable with previous studies, they are in line with findings in previous research in ageing62 or some specific SMI populations 63 64. Further research is needed to understand the potential shared drivers of disability in individuals with BD and these conditions, in general, and diabetes and BD, in particular.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…When we examined the independent association of each physical health condition and disability within groups, our results suggested that sociodemographic factors could have a greater impact in these associations in individuals with SSD. Although our results are not directly comparable with previous studies, they are in line with findings in previous research in ageing62 or some specific SMI populations 63 64. Further research is needed to understand the potential shared drivers of disability in individuals with BD and these conditions, in general, and diabetes and BD, in particular.…”
Section: Discussionsupporting
confidence: 62%
“…Although our results are not directly comparable with previous studies, they are in line with findings in previous research in ageing 62 or some specific SMI populations. 63 64 Further research is needed to understand the potential shared drivers of disability in individuals with BD and these conditions, in general, and diabetes and BD, in particular.…”
Section: Discussionmentioning
confidence: 99%
“…It is equally plausible that poor health could be directly attributed to the consequences of misusing drugs (74). Prior studies have similarly reported poorer quality of life among patients with schizophrenia who were current substance users (75) and among those with current stimulant drug use (76). However, contrary to these findings, the study by Herman (77) found that inpatients with comorbid schizophrenia and substance abuse disorder reported better quality of life than those non-substance abusing inpatients.…”
Section: Discussionmentioning
confidence: 97%
“…Positive symptoms recurrence indicated that patients might stop or discontinue their medication (Kikkert & Dekker, 2017;Vassileva et al, 2014). Meanwhile, schizophrenia patients who had comorbid physical illnesses such as diabetes, hypertension, and cardiovascular disease tended to terminate taking polymedication (Desalegn et al, 2020;MacEwan, Silverstein, Shafrin, Lakdawalla, Hatch, & Forma, 2018). Evidently, re-hospitalization, relapse, and medication non-adherence were related to mental health-care services.…”
Section: Discussionmentioning
confidence: 99%